The unstoppable wasp (2017), volume 1 ebook - Whitley, Jeremy (The Unstoppable Wasp (2017), 2017)
Collects The Unstoppable Wasp #1-4; All-New, All-Different Avengers #14. Nadia spent the entire first half of her life a captive of the Red Room, but now this teenage super scientist is spreading her wings! Hank Pym's daughter has a lot of time to make up for, and she's determined to change the world. With Jarvis at her side, she's on a mission to bring together the brightest girl geniuses of the Marvel Universe - starting with Lunella Lafayette, the miraculous Moon Girl! But Nadia didn't count on evil scientists, man-eating giant rats or Devil Dinosaur - or the lethal lady wrestlers known as the Grapplers! And even as Nadia's recruiting drive continues, the Red Room is on her trail - and they'll pull out all the stops to get her back! Can the geniuses of G.I.R.L. find a way to save Nadia from being dragged back to the bunker? Author: Jeremy Whitley. Illustrator: Elsa Charretier. © 2020 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com